Representasi Tokoh Drupadi Pada Desain Artwear Melalui Kajian Semiotika Roland Barthes - Nadia Rachmaya Ningrum Budiono; Haidarsyah Dwi Albahi (Besaung : Jurnal Seni Desain dan Budaya, 2026)
The legendary Drupadi, which is derived from the Mahabharata's narrative is almost always recited in a traditional manner, and the only reason it is done thus is to serve as a symbol of men's and women's feelings of love and affection. But in the dynamics of contemporary society today, there is a great urgency to reconstruct that image such that it is still relevant to present issues related to empowerment and complexities of women’s identity. In order to provide a solution, this research utilises artwear designs as a form of presentation with the purpose of introducing the character of Drupadi to the metropolitan population. aimed at making the character of Drupadi a symbolic depiction of women’s strength and empowerment in present socio-cultural realities. This Kreative process utilises the method of creation by Prof Dharsono which is done in 4 systematic stages, namely observation, experiment, contemplation and formation. The researcher can dissect the depth of meaning of the character and analyse the denotative and connotative codes of each visual element contained in the artwear design by using Roland Barthes’ semiotic approach. This research through visual exploration of form and colour results in artwear designs that not only emphasise the aesthetic aspect but also convey a deep message about the firmness of identity. The analysis results suggest the visual element is effective in communicating the shift in meaning from passive compliance to active power. The conclusion is that this artwear design has successfully worked as an effective visual communication medium and symbolic element that reflects the Reposisi and identity of women in the midst of heterogeneity of urban society nowadays